Rationale of Policy Reviews for Economic Development: The Case of SME Development Policy of 2003 - Ngowi, Honest Prosper (Journal of Policy and Leadership, 2018)
Tanzania has about five key development policies framework; 16 economic sector policies; about 18 cross-cutting sector policies and 16 sector policies as per January 2016 when this paper was written. For policies to bring about the desired contribution in social-economic development, they need to be well developed and implemented properly. However, for realisation of sustainable economic development to happen, periodic reviews are necessary. In this work, the author makes the need for periodic policy reviews while utilising the Tanzania’s Small and Medium Enterprises Development Policy of 2003 as a case. In the context of this paper, policy review is taken to mean a regular critic and analysis of existing policy in order to make the policy in question relevant and meaningful given the prevailing dynamic situation as opposed to static policy environment during its establishment.The review process was very participatory, inclussive, consultative and constructively process. The paper is based on secondary data, and content analysis.